Seroprevalance of Brucellosis and Q-fever in water buffaloes (Bubalus bubalis) in Haryana state, India. - Dharanya Muthiah; Mahavir Singh; Rajesh Chhabra; Renu Gupta; Swati Dahiya; Priya; Jinu Manoj (PLoS ONE)
Brucellosis and Q-fever are two highly contagious bacterial diseases with significant zoonotic potential and economic threats, yet they often remain underreported and neglected in low- and middle-income countries. The present study aimed to determine the seroprevalence of Brucellosis and Q-fever in water buffaloes in the Haryana state of India to implement effective preventive measures for disease control. The study covered all 22 districts of Haryana and involved 400 serum samples collected from female buffaloes belonging to two age groups and three distinct agro-climatic zones. The collected sera were tested using the Rose Bengal Plate agglutination test (RBPT) and commercial indirect enzyme linked immunosorbent assay (i-ELISA) for the presence of antibodies against smooth strains of Brucella spp. Additionally, the same serum samples were examined by i-ELISA for antibodies against Coxiella burnetii. The overall seroprevalence of brucellosis was observed as 8.25% (CI: 5.75-11.39) using the RBPT and 7.5% (CI: 5.12-10.53) by i-ELISA. The overall observed seroprevalence of Q-fever was 2.00% (CI: 0.87-3.90). No significant variation was seen in seropositivity of both diseases based on age and agroclimatic zones of the state. The findings of this study provide critical insights to farmers, agricultural organizations, veterinary services, and healthcare providers, facilitating more effective implementation of disease control measures.